Flash Drive Communication Using Embedded System (International Journal of Engineering and Computer Science, 2014)
In the modern era the popularity of the Universal Serial Bus storage device is very vast. But disadvantage of USB is that being a peripheral device, it needs a host usually a PC to initiate and mediate communications between two USB storage devices. With help of this project two USB can communicate directly without PC. USB devices directly connected to embedded system. There is a controller that hosts the flash devices. Insert pen drive into USB port, then an signal will sent to the processor indicating that source pen drive is inserted so now processor  will wait for the signal from other USB device. When the controller gets the signal from other USB drive then controller is ready to transfer the data between two. Controller gets the input only from external hard key from the user. Once the user presses the hard key, controller gets the information to transfer the data between two drives. The user interface consists of keypad 20x2 LCD display. User can see the data of both the flash drive and can send in either direction from first flash drive to other or from second to first